Existência de soluções para um problema do tipo (p; q)-Laplaciano com perturbação - Somavilla, Fernanda (2015)
In this paper, considering _ RN (N > 2) a bounded smooth domain, using blow-up techniques and the Leray Schauder Topological Degree theory, we intend to ensure the existence of positive solutions for a problem involving the p-Laplacian operator. Moreover, we employ variational methods, such as the Mountain Pass Theorem, to establish a result of existence and multiplicity of solutions to the following problem with a perturbation term _pu _qu = _u_ + (a(x) + ")ur where 1 < q 6 p < _ + 1 < r + 1 < p_ and the parameters _; " > 0. The function a(x) 2 C1;_() is continuous, nonnegative and it vanishes in a subdomain of .